More appropriate disease control policies for the developing world - Mariner, Jeffrey C. (AOSIS, 2009)
Investment in disease control should be targeted to critical points that provide the greatest benefit to the livelihoods of livestock-dependent stakeholders. Risk-based targeting should balance the impacts of diseases against the feasibility of their control. This requires sensitive and specific surveillance systems that provide representative overviews of the animal health situation for accurate assessment of disease impact and transmission patterns. Assessment of impact should include household and market effects. The key in surveillance is involving livestock owners using active methods that ensure their disease priorities are addressed. Epidemiological targeting of interventions to critical points in disease transmission cycles should be done to obtain maximal disease reduction. Interventions should be delivered in full partnership with both private and community-based stakeholders to assure high uptake and sustainability. In developing countries, approaches such as participatory disease surveillance and community-based animal health programs have been effective and comply with international animal health standards.